Variations on Undirected Graphical Models and their Relationships - Heckerman, David; Meek, Chris; Richardson, Thomas (2004)
We consider undirected graphical models for discrete, finite variables. Lauritzen (1996) provides alternative definitions of such models and describes their relationships. We extend his analysis by considering another definition describing conditionally specified distributions. We describe the relationship of this model class with the previously described classes. In addition, we show that all definitions capture the same set of strictly positive distributions.